Rotatividade docente na rede estadual de educação de Minas Gerais: processos de organização e reorganização pedagógica - Adilson Alves (2023)
The extensive academic production that has teaching work as its object has presented, in recent years, the turnover phenomenon as an important issue in analyzes of the organization and pedagogical planning in public basic schools. . Research has addressed different aspects of this phenomenon, among the most frequent causes pointed out for teacher turnover, the precariousness of working conditions, low pay, lack of recognition and professional devaluation of teachers, progressive salary losses, lack of job and salary plans and increase in temporary contracts (SELLA, 2006, OLIVEIRA 2004, VICENTINI ; LUGLI, 2009). High teacher turnover can compromise the organization of pedagogical work at school and interfere with the teaching-learning process, since pedagogical proposals are based on teaching/learning assumptions that are based on a didactic sequence. The interest in the subject arises from the greatest difficulty I encounter in my work as a non-effective teacher, which is to keep changing schools at the end of my contract, and with that, the teaching-learning process and the affective bonds built throughout are interrupted. from work. The theme chosen is directly related to my trajectory in education. It is precisely this perception of the school reality built throughout my professional experience, reinforced by indicators of the precariousness of work that instigate me for this research.The phenomenon of turnover occurs in the scope of work in general, but in schools it has become a problem at the national level, considering the time of the master's degree, I opted for a geographical cut in the state of Minas Gerais to carry out this study. This research aims to identify and analyze teacher turnover in the State Education Network of Minas Gerais, considering its implications for the administrative and pedagogical dimensions. The universe of analysis refers to two State Schools, both located in the municipality of Betim/MG. In methodological terms, this is a qualitative study. Documentary research and semi-structured interviews were used as data collection instruments. The documentary research was carried out through the analysis of documents such as norms and regulations, among others, related to the object of study. The semi-structured interviews were applied to directors and pedagogues involved in the researched theme, with previously defined questions, but allowing the inclusion of new questions during the interview. The interviews were audio recorded and later transcribed for analysis. The collected data were treated descriptively, through direct and interactive contact with the situation under study. As a result, it is evident the difficulty of guaranteeing the continuity of the teaching-learning process when there are constant changes of teachers. The implications of teacher turnover are many and varied, directly affecting the quality of teaching and student learning, in addition to generating negative impacts on teacher performance and school management.